Design, Synthesis and Biological Activities of Novel Anthranilic Diamide Insecticide Containing Trifluoroethyl Ether - 赵毓 李永强 熊丽霞 王红学 李正名 (Chinese journal of chemistry, 2012)
Two series of novel anthranilic diamide insecticide containing trifluoroethyl ether were designed and synthesized, and their structures were characterized by 1H NMR spectroscopy, elemental analysis and single crystal X-ray diffraction analysis. The insecticidal activities of the new compounds were evaluated. The results of bioassays indicated that some of these title compounds exhibited excellent insecticidal activities. The insecticidal activities of compounds 19a, 19b, 19d, 19g, 19k and 19m against oriental armyworm at 2.5 mg·kg-1 were 100%. The larvicidal activities of 19a, 19b, 19c, 19d, 19e, 19g and 19n against diamond-back moth were 100% at 0.1 mg·kg-1. Surprisingly, most of them still exhibited perfect insecticidal activity against diamond-back moth when the concentration was reduced to 0.05 mg·kg-1, which was higher than the commercialized Chlorantraniliprole.